PERMUKIMAN EROPA SEKITAR TOENTANGSCHEWEG KOTA SALATIGA 1917-1942 - Widayanti, Indina Rizqi; Witasari, Nina (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2024)
The construction of a private farm in Salatiga has made Salatiga magnet for immigrants from outside the city. Population growth has forced the government to provide land for settlement. These immigrants are usually Europeans who work on farms. The land at Toentangscheweg, previously used for coffee farming, has been converted into exclusive settlement for the European elite Toentangscheweg has been transformed into an area with complete facilities and beautiful surroundings with strong and majestic European architectural buildings. The purpose of this research is to determine the development of European settlements in Salatiga. The study uses historical research methods, with stages; heuristic, criticism, interpretation, and historiography. The results of this study show that European settlements have many differences from other inhabitants, especially indigenous people. The life of the Europeans in Toentangscheweg depicts their caste higher than that of the natives. The difference can be seen in housing, vehicles, lifestyles, education, and so on.